Effect of Competence on Satisfaction and Motivation At the Police of the Police Performance Karanganyar - Sriyana, Jaka (STIE AUB Surakarta)
The aim in this study was to determine and analyze the Influence Competence Satisfaction and Motivation In Karanganyar Police Performance Police officers. The population in this study is the police officers at the police station Karanganyar some 400 police officers. Researchers took a sample of 10% that is 400x10% = 40 respondents with a random method that the number of random sampling. So that the number of samples in this study amounted to 40 police officers at the police station Karanganyar. This study uses analysis tools such as validity, reliability, linearity test, path analysis, multiple linear regression analysis, t-test, F and coefficient of determination. The results showed that the competencies and significant positive effect on job satisfaction. Competence positive and significant impact on the motivation. Competence positive and significant effect on performance. Job satisfaction and significant positive effect on performance. Motivation positive and significant effect on performance. F test can be concluded jointly competence variables, job satisfaction and motivation affect the performance of the Police at the Police Karanganyar. R2 value can be interpreted totaling 0.947 variation of the Police Performance in Karanganyar Police explained by the variable competence, job satisfaction and motivation of 94.7% and the remaining 5.3% described other variables outside the model study as an example of training and career path. Results of path analysis, it can be concluded that the use of an intervening variable motivational variables as the most effective way to improve performanceÂ Keywords: Competence, Job Satisfaction, Motivation, Performance Apparatus